2021
DOI: 10.3390/cancers13143536
|View full text |Cite
|
Sign up to set email alerts
|

How May Ramucirumab Help Improve Treatment Outcome for Patients with Gastrointestinal Cancers?

Abstract: GI cancers are characterized by high recurrence rates and a dismal prognosis and there is an urgent need for new therapeutic approaches. This is a narrative review designed to provide a summary of the efficacy as measured by overall survival, progression free survival, and safety data from phase 3 randomized controlled GI clinical trials of ramucirumab including those from important pre-specified patient subgroups and evidence from real clinical practice worldwide. Quality of life (QOL) is discussed where data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Ramucirumab (Eli Lilly), a monoclonal antibody against the receptor VEGFR-2 that effectively neutralizes signal activation by all three extracellular ligands VEGF-A/-C/-D, has been approved for treating gastric cancer, gastro-esophageal junction adenocarcinoma, metastatic non-small cell lung cancer, metastatic colorectal cancer, and hepatocellular carcinoma [ 61 , 62 ]. The efficacy of ramucirumab in clinical practice is similar to that observed in clinical trials [ 63 ]. In metastatic colorectal cancer, ramucirumab is indicated for disease progression after prior therapy with bevacizumab plus chemotherapy [ 61 ], indicating that a more comprehensive blockade of VEGF signaling (VEGF-A/-C/-D vs. VEGF-A alone) may be more beneficial for treatment.…”
Section: Targeting Ligands Vegf-c Vegf-d and Receptors Vegfr-2 And Ve...mentioning
confidence: 55%
“…Ramucirumab (Eli Lilly), a monoclonal antibody against the receptor VEGFR-2 that effectively neutralizes signal activation by all three extracellular ligands VEGF-A/-C/-D, has been approved for treating gastric cancer, gastro-esophageal junction adenocarcinoma, metastatic non-small cell lung cancer, metastatic colorectal cancer, and hepatocellular carcinoma [ 61 , 62 ]. The efficacy of ramucirumab in clinical practice is similar to that observed in clinical trials [ 63 ]. In metastatic colorectal cancer, ramucirumab is indicated for disease progression after prior therapy with bevacizumab plus chemotherapy [ 61 ], indicating that a more comprehensive blockade of VEGF signaling (VEGF-A/-C/-D vs. VEGF-A alone) may be more beneficial for treatment.…”
Section: Targeting Ligands Vegf-c Vegf-d and Receptors Vegfr-2 And Ve...mentioning
confidence: 55%
“…GI cancers are overall the most common causes of cancer-related death in men. [ 20 ] A recent study showed that FOLFIRI is an active and well-tolerated regimen after the failure of a fluoropyrimidine/platinum regimen in patients with advanced gastroesophageal adenocarcinoma. Population with poor prognostic features was well represented.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is one of the major diseases threatening human health, 1,2 and the incidence and mortality have increased rapidly in the past 20 years 3 . There are an average of 12 000 new cancer cases and 10 000 cancer deaths every day, which corresponds to an average of about 7500 cancer deaths every year.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the major diseases threatening human health, 1 , 2 and the incidence and mortality have increased rapidly in the past 20 years. 3 There are an average of 12 000 new cancer cases and 10 000 cancer deaths every day, which corresponds to an average of about 7500 cancer deaths every year. In 2020, there will be an estimated 19.3 million new cancer cases (excluding non‐melanoma skin cancers) and nearly 10 million cancer deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%